Examining the Impact of Covid-19 on Restaurants: the Case of Famagusta/TRNC - Noorafshan, Tina (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In the 21st century, the world is facing a phenomenon called COVID-19, which can be called the most dangerous and challenging human phenomenon after the Spanish flu of 1918-1920. This study aims to investigate the effect of Covid-19 on Famagusta restaurants. Restaurant services and location play an important role in terms of customer experience that can lead to customer satisfaction and loyalty in the restaurant industry in a pandemic. Northern Cyprus government has imposed Movement Control Order (MCO) for preventing the spread of this disease. The main purpose of this thesis is to understand what effects Covid-19 has had on the Famagusta restaurants. By examining how restaurant services work during this pandemic to survive, we can examine the impacts of Covid-19 on restaurants. In between the 14 restaurants interviewed, all of them are in the same location. However, some of them are fast food, some are family restaurants, and some have a brand, which we will see the effects of the pandemic have almost the same effect on Famagusta restaurants. However, the reactions of restaurant owners before these challenges are similar in some cases. In this dissertation, we will explain more about their problems and their acts, according to interviewed with Famagusta restaurant owners/managers. To better understand the impact of covid-19 on restaurants in Famagusta/TRNC, we used a qualitative method to conduct face-to-face interviews.

ÖZ: 21. yüzyılda dünya, 1918-1920 İspanyol gribinden sonra en tehlikeli ve zorlu insan olgusu olarak adlandırılabilecek COVID-19 adlı bir fenomenle karşı karşıya. Bu çalışma, Covid-19'un Gazimağusa restoranları üzerindeki etkisini incelemeyi amaçlamaktadır. Restoran hizmetleri ve lokasyon, bir pandemide restoran endüstrisinde müşteri memnuniyetine ve sadakatine yol açabilecek müşteri deneyimi açısından önemli bir rol oynamaktadır. Kuzey Kıbrıs hükümeti, bu hastalığın yayılmasını önlemek için Hareket Kontrol Emri (MCO) koydu. Bu tezin temel amacı Covid-19'un Gazimağusa restoranları üzerindeki etkilerini anlamaktır. Bu salgın sırasında restoran hizmetlerinin hayatta kalmak için nasıl çalıştığını inceleyerek, restoranlar üzerindeki etkisini inceleyebiliriz. Görüşme yapılan 14 restoran arasında, aynı lokasyonda ve bir markaya sahip olduğu söylenebilir, ancak farklı etkiler yaşadı. COVID-19'un restoranlar üzerindeki etkisini daha iyi anlamak için, yüz yüze görüşmeler yapmak için nitel bir yöntem kullanıldı.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Supervisor: Prof. Dr. Habib Alipour
Keywords: Tourism Faculty; COVID-19 Pandemic--Tourism--Rstaurants--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Effect of covid-19, tourism sector restaurants, Northern Cyprus, Famagusta